THEORY AND METHOD IN CO-EVOLUTION PARADIGM - I. I. Terlioukovich (Наука и техника)
Logic and methodological analysis of joint nature and society development program  formation has been carried out in the paper. The paper shows the role of theory as means of scientific cognition. The paper considers methodological functions of structural components of theoretical knowledge.